Multiple hunting displays in wild broadclub cuttlefish - Martin J. How; Cedric van den Berg; Michael Karcz; Charlie Heatubun; Matteo Santon (Ecology, 2025)

Polarization vision in terrestrial hermit crabs - Martin J. How; Alasdair Robertson; Samuel P. Smithers; David Wilby (Journal of Comparative Physiology A, 2023)
Polarization vision is used by a wide range of animals for navigating, orienting, and detecting objects or areas of interest. Shallow marine and semi-terrestrial crustaceans are particularly well known for their abilities to detect predator-like or conspecific-like objects based on their polarization properties. On land, some terrestrial invertebrates use polarization vision for detecting suitable habitats, oviposition sites or conspecifics, but examples of threat detection in the polarization domain are less well known. To test whether this also applies to crustaceans that have evolved to occupy terrestrial habitats, we determined the sensitivity of two species of land and one species of marine hermit crab to predator-like visual stimuli varying in the degree of polarization. All three species showed an ability to detect these cues based on polarization contrasts alone. One terrestrial species, Coenobita rugosus , showed an increased sensitivity to objects with a higher degree of polarization than the background. This is the inverse of most animals studied to date, suggesting that the ecological drivers for polarization vision may be different in the terrestrial environment.

Visual noise from caustic flicker does not affect the hunting success of cuttlefish - Christian Drerup; Martin J. How; James E. Herbert-Read (Animal Behaviour, 2023)

Gaze stabilization in mantis shrimp in response to angled stimuli - Ilse M. Daly; Martin J. How; Julian C. Partridge; Nicholas W. Roberts (Journal of Comparative Physiology A, 2019)

Correction to: Polarisation vision: overcoming challenges of working with a property of light we barely see - James J. Foster; Shelby E. Temple; Martin J. How; Ilse M. Daly; Camilla R. Sharkey; David Wilby; Nicholas W. Roberts (The Science of Nature, 2018)

Polarisation vision: overcoming challenges of working with a property of light we barely see - James J. Foster; Shelby E. Temple; Martin J. How; Ilse M. Daly; Camilla R. Sharkey; David Wilby; Nicholas W. Roberts (The Science of Nature, 2018)

Systematic variations in microvilli banding patterns along fiddler crab rhabdoms - Ali Alkaladi; Martin J. How; Jochen Zeil (Journal of Comparative Physiology A, 2013)

Variability of a dynamic visual signal: the fiddler crab claw-waving display - Martin J. How; Jochen Zeil; Jan M. Hemmi (Journal of Comparative Physiology A, 2009)

Courtship herding in the fiddler crab Uca elegans - Martin J. How; Jan M. Hemmi (Journal of Comparative Physiology A, 2008)

Differences in context and function of two distinct waving displays in the fiddler crab, Uca perplexa (Decapoda: Ocypodidae) - Martin J. How; Jochen Zeil; Jan M. Hemmi (Behavioral Ecology and Sociobiology, 2007)